Suppose $f:\mathbb{R}^2\to\mathbb{R}$ defined by $f(x,y) = \frac{x^2y}{x^2+y^2}$, such that $x^2+y^2>0$ and $f(0,0) = 0$. Show that for every path $\lambda:(-\epsilon,\epsilon)\to\mathbb{R}^2$ differentiable at $0$, with $\lambda(0)=(0,0)$, $(f\circ \lambda)'(0)$ exists

For me, this question was just about using the chain rule:

$$(f\circ \lambda)'(0) = f'(\lambda(0))\lambda'(0)$$

Since $\lambda(0)=0$ exists and also $\lambda'(0)$, I should just show that $f$ is differentiable.

I'd first take the partials at $x$ and $y$:

$$\frac{\partial f}{\partial x} = \frac{2xy}{x^2+y^2} - \frac{x^2y}{(x^2+y^2)^2}$$

$$\frac{\partial f}{\partial y} = \frac{x^2}{x^2+y^2} - \frac{x^2y}{(x^2+y^2)^2}$$

Now remember that a function $f:\mathbb{R}^2\to\mathbb{R}$ is differentiable if there exists $r(v)$ such that

$$f(a+v) = f(a) + \frac{\partial f}{\partial x}v_1 + \frac{\partial f}{\partial y}v_2 + r(v)$$

where $\frac{r(v)}{|v|}\to 0$

So solving for $r(v)$:

$$r(v) = f(a+v)-f(a) - \frac{\partial f}{\partial x}(a)v_1 - \frac{\partial f}{\partial y}(a)v_2$$

*where $v = (v_1,v_2)$


$$\frac{r(v)}{|v|} = \frac{f(a+v)-f(a) - \frac{\partial f}{\partial x}(a)v_1 - \frac{\partial f}{\partial y}(a)v_2}{\sqrt{v_1^2+v_2^2}} $$

But the partial derivatives are not defined on $0$, what should I do here?

If the limit of that thing goes to $0$ when $v\to 0$, $f$ is differentiable.


By the comment below, the partials at $0$ are $0$, so we end with the following limit:

$$\lim_{v\to 0}\frac{r(v)}{|v|} = \frac{f(a+v)-f(a)}{\sqrt{v_1^2+v_2^2}} =$$

$$\lim_{(v_1,v_2)\to (0,0)} \frac{v_1^2v_2}{\sqrt{v_1^2+v_2^2}}$$

  • $\begingroup$ For a function $F:U\subset\mathbb R^2\to\mathbb R$ the partial derivatives are defined as $$\frac{\partial F}{\partial x}(a,b)=\lim_{h\to 0}\frac{F(a+h,b)-F(a,b)}{h}\qquad\text{and}\qquad\frac{\partial F}{\partial y}(a,b)=\lim_{k\to 0}\frac{F(a,b+k)-F(a,b)}{k}$$ whenever those limits exist. Then, for the given function we have \begin{align*} \frac{\partial f}{\partial x}(0,0)&=\lim_{h\to 0}\frac{\frac{h^2\cdot 0}{h^2+0^2}-0}{h}=\lim_{h\to 0}\frac{0}{h}=0\\ \frac{\partial f}{\partial y}(0,0)&=\lim_{k\to 0}\frac{\frac{0^2\cdot k}{0^2+k^2}-0}{k}=\lim_{h\to 0}\frac{0}{k}=0 \end{align*} $\endgroup$ – Ángel Mario Gallegos Apr 14 '17 at 22:43
  • $\begingroup$ @ÁngelMarioGallegos thank you! I updated the question with your observation. $\endgroup$ – Guerlando OCs Apr 14 '17 at 23:15

Set $\lambda(t) = (\mu(t),\nu(t))$. For now, assume one of $\mu'(0)$ and $\nu'(0)$ is nonzero.

\begin{align*} (f\circ \lambda)'(0) &=\lim\limits_{h\to 0} \frac{f(\lambda(h))-f(\lambda(0))}{h}\\ &= \lim\limits_{h\to 0}\frac{\mu^2(h)\nu(h)}{h(\mu^2(h)+\nu^2(h))}\\ &=\lim\limits_{h\to 0}\frac{\mu(h)}{h}\frac{\mu(h)\nu(h)}{\mu^2(h)+\nu^2(h)}\\ &=\lim\limits_{h\to 0}\frac{\mu(h)}{h}\frac{\left(\frac{\mu(h)}{h}\right)\left(\frac{\nu(h)}{h}\right)}{\left(\frac{\mu(h)}{h}\right)^2+\left(\frac{\nu(h)}{h}\right)^2} =\mu'(0)\frac{\mu'(0)\nu'(0)}{\mu'^2(0)+\nu'^2(0)}. \end{align*} If $\lambda'(0) = 0$, then $\lim\limits_{h\to 0}\frac{\mu(h)}{h} = 0$ and $\left|\frac{\mu(h)\nu(h)}{\mu^2(h)+\nu^2(h)}\right|\leq\frac12$ is bounded, so $(f\circ\lambda)'(0)=0$. In any case, $(f\circ\lambda)'(0)$ always exists.

If $f$ were differentiable, then applying the chain rule $(f\circ\lambda)'(0) = f'(\lambda(0))\lambda'(0) = 0$ for every $\lambda$. However, if we take $\lambda(h) = (h,h)$, we have $(f\circ\lambda)'(0)=1/2$. This means that $f$ is not differentiable.

The point of this exercise is to show you that even if $f:\mathbb R^2\to\mathbb R$ is differentiable in every direction (the direction if $\lambda'(0)$ for every $\lambda$, in this case) it might not be differentiable in the linear map sense. You cannot use the chain rule if you don't know $f$ is differentiable to begin with.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.